Jawaharlal Nehru and the Planning Commission - Planning Commission (Planning Commission, 1964)
“Jawaharlal Nehru and the Planning Commission” traces the intellectual and political evolution of Jawaharlal Nehru’s commitment to planned economic development and his central role in institutionalizing planning in independent India. Beginning with his early engagement with agrarian distress in the 1920s and influenced by his exposure to European socialist ideas, Nehru came to view political independence as inseparable from social and economic transformation. His advocacy for state ownership of key industries, articulated in the 1929 Congress resolution and reinforced at the Karachi Session of 1931, laid the ideological foundation for a socialist-oriented development model centered on large-scale industrialization and scientific progress. As Chairman of the National Planning Committee in 1938 and later instrumental in establishing the Planning Commission in 1950, Nehru championed coordinated state planning as essential for overcoming poverty, inequality, and economic backwardness. He envisioned a balanced approach integrating heavy industry with cottage sectors, guided by democratic principles and public participation, and aligned planning objectives with the Directive Principles of State Policy. Despite bureaucratic resistance and political challenges, including the aftermath of the 1962 conflict, Nehru remained steadfast in promoting scientific modernization, community development, and strategic industrial growth. His leadership firmly embedded planning within India’s democratic framework, shaping the nation’s economic trajectory through a synthesis of socialism, science, and participatory governance.
Indian Institute of Public Administration
Indian Institute of Public Administration
Keywords: Jawaharlal Nehru; Planning Commission of India; National Planning Committee 1938; Socialist Economic Vision; Democratic Planning; Industrialization Strategy; State Ownership of Industries; Karachi Resolution 1931; Advisory Planning Board 1946; Scientific and Technological Development; Community Development Programme; Directive Principles of State Policy